Robot Controller and Manipulator - Md Zin, Zulkifli (Universiti Teknologi Petronas, 2004)
This project, entitled Robot Controller and Manipulator comprises of development of a manipulator and controller. The project scopes are to develop an articulated manipulator with three degrees of freedom (3-DOF), a PC-based robot controller, capability of robot to determine path plan and some graphical user interfaces. The invention of robot manipulator aggressively carried out during the industrial revolution, starting from twentieth century. The robot manipulator is extensively used in industry since it is believed that its implementation has several advantages over conventional ways, such as several jobs executed by human are very dangerous, designed components are sometimes having defects and long period of time taken to execute repetitive jobs. Generally, the scope of this project is to develop 3-DOF robot manipulator by considering dynamic properties. 3-DOF is purposely for positioning function. If the manipulator is needed to be equipped with manipulating function, it is required higher than 3-DOF system, usually 6-DOF. The project is divided into two parts; manipulator design and controller design. The manipulator design involves construction of manipulator from suitable material, implementation of forward and reverse kinematics, workspace determination, movement analysis and finally integration of the designed components. The controller design consists of development of dc motor drive system, controller chip by using PIC microcontroller, motor feedback system and graphical user interface at host PC. The user will control the manipulator through this user interface and this host PC will communicate with PIC microcontroller through serial communication.